(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This paper seeks to raise the question of the self as understood theoretically within existential therapeutic literature and as experienced phenomenologically in our everyday lives and to look at the relevance of this to psychotherapy.